2010
DOI: 10.2152/jmi.57.179
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea induced by infection of <I>Vibrio parahaemolyticus</I>

Abstract: Many species of bacteria induce secretory and inflammatory diarrhea (1). The increased intestinal fluid secretion in diarrhea appears to result from the active secretion of chloride (1-3), a principal anion, but the way in which diarrhea is caused by individual bacterial infections has not been completely elucidated. Vibrio parahaemolyticus is a Gram-negative halophilic bacterium that naturally occurs in marine and estuarine environments (4). It is a human pathogen that causes food-borne acute gastroenteritis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…The TDH is encoded by the tdh gene, and subsequently a related gene, termed the tdhrelated hemolysin (trh), was identified (26). Together, tdh and trh are widely considered the predominant indicators of strain virulence in V. parahaemolyticus (26,37,38). This is substantiated by the prevalence of tdh and/or trh in clinical V. parahaemolyticus isolates and the infrequent detection of these virulence markers in food and environmental samples (9,27,28,35,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The TDH is encoded by the tdh gene, and subsequently a related gene, termed the tdhrelated hemolysin (trh), was identified (26). Together, tdh and trh are widely considered the predominant indicators of strain virulence in V. parahaemolyticus (26,37,38). This is substantiated by the prevalence of tdh and/or trh in clinical V. parahaemolyticus isolates and the infrequent detection of these virulence markers in food and environmental samples (9,27,28,35,40).…”
mentioning
confidence: 99%
“…A recent review of the pathogenicity effects of individual factors concluded that deletion of tdh does not affect cytotoxicity, indicating that the virulence of V. parahaemolyticus involves more than just the presence of tdh and/or trh (2). The type III secretion system (T3SS) of V. parahaemolyticus has been investigated as a potential indicator of strain virulence (2,33,37). Two nonredundant T3SSs can be found in many V. parahaemolyticus strains (2,33).…”
mentioning
confidence: 99%
“…However, V. vulnificus infections can be more severe, potentially leading to sepsis and death (5, 6). The approximate case fatality rate for V. vulnificus infections is 35%, making it the most deadly food-borne pathogen (3).Pathogenicity of V. parahaemolyticus is generally associated with the presence of the thermostable direct hemolysin (tdh) and/or the tdh-related hemolysin (trh) genes (2,(7)(8)(9). Although recent evidence suggests that there may be additional factors responsible for differential virulence of this organism (10, 11), the tdh and trh genes remain the most reliable indicators of virulence currently available.…”
mentioning
confidence: 99%
“…Vibrio parahaemolyticus is a gram-negative, halophilic bacterium that occasionally infects humans via wounds or consumption of contaminated seafood [1], and often leads to acute gastroenteritis and other serious diseases including septicemia in aquatic species [2,3]. The harmful outcomes caused by this bacterium are increasingly becoming serious, especially in coastal waters and fish farms [4].…”
Section: Introductionmentioning
confidence: 99%